SYSTEMIC BASES OF STATE REGULATION OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Sabaydullaeva Marxamat Abdulkhodievna; Umurzakov Dilshodbek Khakimovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the basics of systems of state regulation of small business and private entrepreneurship.